Shakedown of bolts with a one-sided propagating crack - Leonavičius, Mindaugas; Sušukšta, Marijonas (Journal of Civil Engineering and Management, 2002)
Cyclic strains of joints may cause formation of a crack or cracks in a bolt thus changing its loading conditions. After crack appearance in a bolt it can be used if its length does not exceed a critical one. Modification of the shakedown theorem – the method of additional load – was applied in the investigation. The results – the analytical expressions of shakedown conditions are in a sufficiently good agreement with those achieved by other methods. Differences occur due to failure to get an accurate analytic expression. Solution of the shakedown problem plays an essential role in determining the safety factor of bolts subjected to cyclic strains.Frist Published Online: 30 Jul 2012